PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS KEARIFAN LOKAL MATA PELAJARAN IPAS TEMA INDONESIAKU KAYA BUDAYA KELAS IV SD NEGERI SIDOREJO: Pengembangan - Betti Dwi Wardaningsih; Titi Anjarini; Nur Ngazizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to: 1) Produce a Local Wisdom-Based Learning Module for the Social Studies Subject with the Theme "My Indonesia is Rich in Culture" for Grade IV of Sidorejo Elementary School. 2) Determine the feasibility of the developed module. This development model uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The subjects in this study were 15 fourth-grade students at Sidorejo Elementary School. Data collection techniques used were observation, interviews, questionnaires, documentation, and tests. The instruments used were validation questionnaires from material experts, media experts, and practitioners, student responses, learning implementation sheets, and tests. The results of this development research are: 1) a local wisdom-based module with the Theme "My Indonesia is Rich in Culture" for Grade IV of Sidorejo Elementary School. 2) The module's feasibility, based on validation results from material experts, was 85% valid, with media experts 85% valid, and practitioners 95% very valid. The module's practicality, based on student responses from limited trials, was 85% very practical, and from extensive trials 87% very practical. The implementation results from limited trials were 85% very practical, and from extensive trials 93% very practical. The module's effectiveness, based on student test results after using the module, obtained an average N-gain of 0.73 for limited trials, with a high criterion, and an estimated N-gain percentage of 73%, with an effective criterion. Meanwhile, the extensive trials obtained an average N-gain of 0.75, with a high criterion, and an estimated N-gain percentage of 75%, with an effective criterion. Based on the statement above, this module is declared feasible.